Multi-Objective Optimal Tuning Framework of the Entire PMSM-Driven Servo System Considering High-Frequency Disturbance Suppression - Zihan Tang; Liping Wang; Jihui Han; Dong Wang; Xuekun Li (IEEE Access)
A universal PMSM-driven servo system comprises cascaded PI controllers with a low-pass speed filter for high-frequency disturbance suppression. However, the speed filter and the current loop have received limited attention during the tuning of the speed loop, potentially leading to high-frequency fluctuations or significant resonances in the entire servo system under disturbances. This paper proposes a novel framework of multi-objective optimal tuning for the entire PMSM-driven servo system, focusing on suppressing high-frequency disturbances. The controller parameters to be tuned include the PI gains of the speed loop, the filter time constant and the equivalent time constant of the current loop. The closed-loop cut-off frequency of disturbances is established as a constraint to optimize the speed filter, and the current loop time constant is selected as an objective to improve control smoothness. Experimental results demonstrate that the proposed method can reduce the high-frequency fluctuations of speed and current without causing system resonances.